Ethnobotanical wisdom in phytocosmeceuticals: Investigating pharmacological applications in Western Odisha, India - Acharya, Biswajeet; Behera, Adyasha; Mohanty, Parimita; Sahu, Smrutirekha; Padhan, Truptipragyan; Mishra, Durga Prasad; Behera, Amulyaratna; Sahu, Prafulla Kumar (Ethnobotany Research and Applications, 2025)
Background: Ethnobotany bridges traditional knowledge with modern science, focusing on the sustainable use of plants. Phytocosmetics, derived from plant-based bioactive compounds, offer eco-friendly alternatives to synthetic cosmetics. This research documents and analyzes tribal knowledge of phytocosmetics in western Odisha, identifying plant species, preparation methods, cultural significance, and potential for sustainable, eco-friendly cosmetic development. Materials and Methods: An ethnobotanical survey was conducted across six districts in Western Odisha, engaging 112 tribal informants through semi-structured interviews and focus group discussions. Plant specimens were collected and identified, and their cultural and pharmacological uses were documented. Quantitative indices such as Use Value (UV), Relative Frequency of Citation (RFC), and Fidelity Level (FL) were used to analyze the data. Results: A total of 39 plant species were obtained from 33 different families. Key plants identified include Aloe barbadensis, Azadirachta indica, Curcuma longa, and Hibiscus rosa-sinensis. These plants are commonly used in skin moisturizers, antimicrobial preparations, anti-aging formulations, and hair care products. Santalum album exhibited the highest UV (0.93) and RFC (0.98) values, while its FL (97%) underscored its strong association with anti-inflammatory and skin-conditioning applications. Other notable plants, such as Curcuma longa and Rubia tinctorum, demonstrated high FL values, reflecting their specific roles in skin brightening and rejuvenation. Their pharmacological properties are mediated through pathways such as NF-κB and Nrf2, supporting their efficacy in skincare and haircare. Conclusion: The study highlights the relevance of traditional phytocosmetic practices in modern applications, emphasizing the importance of conservation and sustainable development. Integrating tribal knowledge with advanced technologies, such as nanotechnology, offers the potential for innovative, eco-friendly cosmeceuticals. Keywords: Ethnobotany, Phytocosmetics, Western Odisha, Sustainable Development, Biodiversity Conservation.